Comparação de características estruturais e funcionais de espermatozoides bubalinos com maior ou menor sensibilidade à criopreservação - Beatriz Parzewski Neves (2019)
This study aimed to evaluate the structural and functional differences in buffalo sperm that could influence its resistance to the freezing-thawing process. A total of 90 ejaculates, collected by artificial vagina method from 13 Murrah buffalo bulls (Bubalus bubalis), were evaluated, diluted in Tris-citric acid-fructose containing 10% of low-density lipoproteins extender and submitted to the freeze-thaw protocol. Computer Assisted Sperm Analysis (CASA) was undertaken in six different moments during the process: pre-cooling (PC), pre-freezing (PF) and five, 60, 120 and 180 minutes after thawing under incubation at 37 °C (PT_T5, PT_T60, PT_T120 and PT_T180, respectively). Sperm resistance to freezing-thawing was calculated for each ejaculate by the difference between total motility at PC and that at PT_T180 moment. Two groups of divergent sperm freezing-thawing resistances were then created: RB group (n=23) was composed by the ejaculates that had lost less than 41,2% of total motility and RR group (n=22) was composed by the ejaculates that had lost more than 65,1% of total motility. Flow cytometry analyses were performed for each ejaculate using the respective fluorescence probe: plasmatic and acrosomal membrane integrity (MPA; IP and FITC-PSA), plasmatic membrane stability (YOPRO-1), mitochondrial membrane potential (HPM; MitoStatus Red), intracellular hydrogen peroxide production (H2O2; CM-H2DCFDA), superoxide anion production (O2•-; MitoSOXTM Red) e lipid peroxide (LPO; C11-BODYPY). For all analyses, p≤0,05 was considered as significant. Progressive motility and the kinematic parameters VCL, VSL, VAP, BCF and ALH were lower in RR sperm cells, mainly on the post-thawing incubation moments. MPA and plasmatic membrane stability values were also lower in RR group at the both post-thawing evaluation times, PT_T5 and PT_T180. Besides, mitochondrial metabolism was lower in RR spermatozoa as lower values of the percentage of cells with HMP and, HMP intensity in intact cells at PT_T5 and PT_T180 and in non-intact cells at PT_T5 were observed in that group. Superoxide anion production was found greater, whereas H2O2 production was lower in RR group at the two evaluation times during post-thawing incubation period (PT_T5 and PT_T180). LPO did not differ between groups at PT_T5 and at PT_T180, even after arachidonic acid challenge of sperm cells at PT_T5. This study suggests that differences in sperm freezing-thawing resistance observed between buffalo bull ejaculates are related to plasmatic membrane sensibility and mitochondrial metabolism that results in altered motility and kinematic parameters, but not in oxidative damages as lipid peroxidation.